Assessment of Some Serum Metabolites and Enzymes of Broiler-Chickens Fed Raw and Processed Bambara Groundnut - Oloyede, O.B.; Odutuga, A.A.; Minari, J.B.; Amballi, A.A. (International Journal of Poultry Science, 2007)
Sixty day-old broiler chicks were used in a 4-weeks feed trial to determine the status of raw, roasted and fermented bambara groundnut. The raw and processed bambara groundnuts were used as the sole source of protein in a basal broiler chick starter diet. Soybean based diet served as the control. There were four (4) experimental groups each made up of five birds in three replicates, allocated to the experimental diets. Application of roasting and fermentation techniques were able to reduce the levels of some antinutrients in the bambara groundnut except for oxalate that increased significantly for the fermented sample. The results showed that the serum parameters like total protein, uric acid and creatinine levels indicated that both roasted and fermented based diet fed to the birds were unable to efficiently make available the nutrients in the diets to the birds. Serum transaminases (GOT and GPT) and serum alkaline phosphatase (ALP) showed significant (p<0.05) increase in the activity of the serum of birds fed on roasted and fermented bamabara groundnut based diet. It is therefore concluded that the quality of the protein of the raw and processed bambara groundnut based diet demonstrated inferiority relative to the soybean based diet.